NEW UZBEKISTAN DEVELOPMENT STRATEGY AND WOMEN’S EDUCATION (American Journal of Pedagogical and Educational Research, 2023)
In this article, the attention paid to the education of young women and girls in Uzbekistan today, the essence of the work carried out to support women in all aspects, as well as the important points defined in this regard in the "Development Strategy of New Uzbekistan" tasks mentioned. The article also emphasized the importance of the role of our young scientists in the implementation of the "Third Renaissance" in our country.